Letter from Campbell Morfit to James Curtis Booth, March 13, 1856 - Morfit, Campbell (1856)
Campbell Morfit (1820-1897), a distinguished chemist from the United States, co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry, requests a small aluminum coin from the United States Mint.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Mint of the United States; United States Mint